2014
DOI: 10.1016/j.jbiomech.2014.07.014
|View full text |Cite
|
Sign up to set email alerts
|

The role of transmembrane proteins on force transmission in skeletal muscle

Abstract: Lateral transmission of force from myofibers laterally to the surrounding extracellular matrix (ECM) via the transmembrane proteins between them is impaired in old muscles. Changes in geometrical and mechanical properties of ECM of skeletal muscle do not fully explain the impaired lateral transmission with aging. The objective of this study was to determine the role of transmembrane proteins on force transmission in skeletal muscle. In this study, a 2D finite element model of single muscle fiber composed of my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 28 publications
1
6
0
1
Order By: Relevance
“…Our predictions are consistent with recent studies which determined the influence of transmembrane protein density and stiffness on lateral force transmission [30]. Supporting that study, we found that the stiffness of the protein had minimal effect on the fascicle shear modulus, while the density of proteins significantly affected the fascicle shear modulus.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our predictions are consistent with recent studies which determined the influence of transmembrane protein density and stiffness on lateral force transmission [30]. Supporting that study, we found that the stiffness of the protein had minimal effect on the fascicle shear modulus, while the density of proteins significantly affected the fascicle shear modulus.…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, increasing the volume fraction of ECM could be paired with changes in collagen content and architecture, which would also influence the tissue-level properties and potential damage sensitivity of the membrane. Further, the mechanical properties of the transmembrane proteins were represented using a continuous nonlinear curve [30], although physiological models often represent it as a piecewise function due to the unfolding of the protein [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, disorganization of sarcomeres due to the lack or presence of desmin aggregates generates a defect in force production ( Li et al, 1997 ; Anderson et al, 2002 ) that causes the muscle weakness observed in patients. However, force transmission is not only longitudinal to the tendon ( Sharafi and Blemker, 2011 ), but also lateral from costameres to the endomysium ( Zhang and Gao, 2014 ). Thus, reduced force production and altered force transmission would generate significant muscle weakness in patients.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the cell response is also dependent on the contractile forces present in the intracellular matrix of the cell. The mechanotransduction process is regulated by the cross-talk between ECM and ICM, implying different transmembrane proteins, such as dystroglycan, sarcoglycans or intergrins, for instance [ 78 , 147 , 148 ]. For the striated muscle cells, the mechanical cross is mainly between ECM and ICM in the skeletal muscle, while in the heart, there is an additional cross-talk between the cells.…”
Section: Muscle Lim Proteinmentioning
confidence: 99%